THE USE OF MODERN INFORMATION TECHNOLOGY IN PEDAGOGY - Kenjebayeva Gulnur Maratovna (Zeta Repository, 2023)
Today in our country, equal attention is paid to all areas. In particular, the field of Education. That is why pedagogy is important as a programming area in the training of young professionals. In particular, the use of modern technologies in the education and education of young people, their introduction into education has become a priority. In this article, the author covers in detail the role of pedagogical technologies and modern technologies in pedagogy.